Analisis Pesan Akidah dalam Konten Animasi Pada Akun TikTok @CulapCulip Bulan Oktober – Desember Tahun 2023 - Azwan Ali (Sekolah Tinggi Agama Islam As-Sunnah, 2025)
Da'wah (Islamic propagation) can be carried out by anyone, using any media, as long as it is permitted by Islamic law. In recent times, many people have used various media for da'wah, one of which is the social media platform TikTok. However, it is rare for people to use animated videos as a medium for conveying da'wah, as seen in the TikTok account @CulapCulip. Therefore, this study aims to explore the messages of aqidah (Islamic creed) in the animated content of the TikTok account @CulapCulip. This research is a content analysis that employs a qualitative descriptive approach, with the primary data source being the TikTok account @CulapCulip. The data collection technique used is coding sheet. The results of the study conclude that the animated content of CulapCulip from October to December 2023 contains messages of aqidah, including ilahiyat (theology), nubuwat (prophethood), ruhaniyat (spirituality), and sam'iyyat (auditory aspects), with the message of sam'iyyat dominating the other messages, totaling 10 messages or 50%. This is followed by ilahiyat messages, totaling 6 messages or 30%, and nubuwat and ruhaniyat messages, each totaling 2 messages or 10% of the total 20 messages.